Fibrinolytic or not : case series of stemi and deadly hemorrhagic stroke - Sidhi Laksono Purwowiyoto; Steven Phillip (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Cardiovascular diseases (CVD) like myocardial infraction (MI) is still becoming the leading cause of morbidity and mortality and major problem in our healthcare system. Nowadays, revolution in high-tech medical treatment alongside with well-trained staff could decrease adverse event in ST elevation myocardial infarction (STEMI) patient. However, in developing country like Indonesia, those still become a challenge. Fibrinolytic therapy is still common practice even though primary percutaneous coronary intervention (PPCI) preferred. Intracranial bleeding is one of the most unfavorable effect after fibrinolytic therapy. Clinical should aware with clinical deterioration. Here we present case series of deadly intracranial haemorrhage in STEMI patient after fibrinolytic therapy.